Raw Material Control and Production Planning to Reduce Excess Finished Products (Case Study: UD. ABC) - Thomas Hadi; Herlina Herlina (JRSI (Jurnal Rekayasa Sistem dan Industri), 2025)
UD. ABC is a manufacturing company that produces multi-purpose shelves and plate racks with a make to stock system. UD ABC faces a mismatch between production volume and actual demand, leading to overproduction, excess inventory, and idle money. This study aims to identify the most accurate forecasting method, develop an optimal production plan, and determine raw material requirements with minimum inventory cost. Demand and production data from April 2025–August 2025 were analyzed using Moving Average, Single Exponential Smoothing, and linear trend, evaluated through MAD, MSE, MAPE, and tracking signal. The selected forecast was used to construct aggregate planning, a Master Production Schedule (MPS), MRP, and safety stock. Results show that the chosen forecasting method reduces deviations between production and demand. The proposed production plan decreases production and storage costs, while MRP yields more efficient raw material requirements. Overall, the proposed planning approach minimizes overstock and improves operational effectiveness.